Activated phosphoinositide 3‐dinase delta syndrome (APDS): An update. (25th January 2022) - Lougaris, Vassilios; Cancrini, Caterina; Rivalta, Beatrice; Castagnoli, Riccardo; Giardino, Giuliana; Volpi, Stefano; Leonardi, Lucia; La Torre, Francesco; Federici, Silvia; Corrente, Stefania; Cinicola, Bianca Laura; Soresina, Annarosa; et al.
Abstract: Activated phosphoinositide 3‐kinase delta syndrome (APDS) is a recently described form of inborn error of immunity (IEI) caused by heterozygous mutations in PIK3CD or PIK3R1  genes, respectively, encoding leukocyte‐restricted catalytic p110δ subunit and the ubiquitously expressed regulatory p85 α subunit of the phosphoinositide 3‐kinase δ (PI3K δ ). The first described patients with respiratory infections, hypogammaglobulinemia with normal to elevated IgM serum levels, lymphopenia, and lymphoproliferation. Since the original description, it is becoming evident that the onset of disease may be somewhat variable over time, both in terms of age at presentation and in terms of clinical and immunological complications. In many cases, patients are referred to various specialists such as hematologists, rheumatologists, gastroenterologists, and others, before an immunological evaluation is performed, leading to delay in diagnosis, which negatively affects their prognosis. The significant heterogeneity in the clinical and immunological features affecting APDS patients requires awareness among clinicians since good results with p110 δ inhibitors have been reported, certainly ameliorating these patients' quality of life and prognosis.